Clinical nursing and midwifery research: grey literature in African countries. (18th January 2016) - Sun, C.; Dohrn, J.; Omoni, G.; Malata, A.; Klopper, H.; Larson, E.
Abstract : Aim: This study reviewed grey literature to assess clinical nursing and midwifery research conducted in southern and eastern African countries over the past decade. Background: The shortage of published nursing research from African countries severely limits the ability of practicing nurses and midwives to base clinical decisions on solid evidence. However, little is known regarding unpublished or unindexed clinical research ('grey literature'), a potentially rich source of information. Identifying these sources may reveal resources to assist nurses in providing evidence‐based care. Introduction: This scoping review of grey literature on clinical nursing and midwifery research in southern and eastern African countries helped to identify gaps in research and assess whether these gaps differ from published research. Methods: Systematic searches of grey literature were performed. Research was included if it was conducted by nurses in 1 of 25 southern or eastern African countries, between 2004 and 2014 and included patient outcomes. Data were extracted on location, institution, research topic, institutional connections and author information. Chi‐square tests were performed to compare differences between indexed and non‐indexed literature. Results: We found 262 studies by 287 authors from 17 southern and eastern African countries covering 13 topics. Although all topics were also found in indexed literature and there were statistically significant differences between the number of times, fewer topics were covered in grey literature vs. indexed. Discussion: Patient satisfaction and experience and traditional health practices were more likely to be published, whereas chronic disease, assault and paediatric‐related research were less often published. Conclusions and Implications for Nursing and Health Policy: Generally, there is a paucity of clinical nursing research in this region. This could reflect the shortage of nurses prepared to conduct research in this region. Nurses may find additional resources for evidence in the grey literature. A complete understanding of the state of nursing science in southern and eastern African countries will help nurses and midwives to understand gaps in clinical research knowledge, potentially direct their research to more critical topics, and inform funding bodies and policy‐makers of the situation of nursing science in southern and eastern African countries.